How Can Different Polishing Timing Influence Methacrylate and Dimethacrylate Bulk Fill Composites? Evaluation of Chemical and Physical Properties. (9th January 2020) - Monterubbianesi, Riccardo; Tosco, Vincenzo; Sabbatini, Simona; Orilisi, Giulia; Conti, Carla; Özcan, Mutlu; Orsini, Giovanna; Putignano, Angelo
Abstract : The polishing procedure is commonly performed after direct composite restorations, and little information exists regarding the right timing during which it should be performed on bulk fill composites. This study investigated the effect of polishing timing on the degree of conversion (DC), Vickers microhardness (VMH), and surface morphology of a methacrylate- (MET-) and dimethacrylate- (DMET-) based bulk fill composite, by using FT-NIR, microhardness tester, and SEM. Composite samples were divided as follows: in Group I (immediate), samples were polished immediately after curing ( t 0 ); in Group D (delayed), samples were polished after 24 h from curing ( t 24 ), whereas the unpolished samples were considered as controls (Group C). The DC and VMH values were evaluated before and after polishing, at t 0 and t 24 . Statistical analysis was performed with a significance level set at p < 0.05 . At t 0, DC increased after polishing in both tested composites (p < 0.05 ), while at t 24, Group I and Group D were not different. By considering VMH, in the case of MET, all groups were not different both at t 0 and t 24 . On the other hand, at t 0, VMH values of DMET increased after polishing. At t 24, DMET Group I and DMET Group D were not different. Qualitative evaluations of scanning electron micrographs showed that the surface morphology of MET presented a more irregular aspect than the DMET one. In summary, since the immediate polishing of MET can improve the DC, without negatively affecting VMH, but showing an irregular surface, it is suggested to wait 24 hours before proceeding with polishing. Otherwise, for DMET, the immediate polishing could definitively be recommended, since it improves both DC and VMH, also producing a regular surface. Therefore, clinicians may always safely polish a restoration performed using DMET-based bulk fill composites in one-chair appointment, avoiding a second appointment.